IMPACT OF CARBURIZING AND BOROSILICONIZING ON VIBROACCELERATION OF BEVEL GEAR FRONT DRIVE AXLE SKIDDERS DURING OPERATION - M. N. Pischov; S. E. Belskiy; E. P. Andreykovets (Литьë и металлургия, 2015)
It is now established that the main causes of failure of the transmission parts of the forest machines is wear of their working surfaces. The destruction of the contact surfaces of bevel gears front axle of skidder TTP-401 during its operation is usually connected, with the formation of plastic deformation on the teeth. According to modern concepts of the theory of the destruction of the details revealed that after the formation of plastic deformations leads to microcracks, the development of micro tracks depends on the magnitude and sign of residual stresses. This article presents dependance graphs of vibration acceleration bevel gears front axle skidder subiect to the method of hardening.